A Unique Numerical Model to Evaluate the Influence of Adherends' Misalignment on Adhesive Joint Strength - Corrado, Andrea; Polini, Wilma (Manufacturing Technology Journal, 2024)
Industry 4.0 needs to have a digital representation of the real manufacturing and assembly processes to foresee the effects of modifications on equipment, tools and processes. Assembly processes often use adhesive to keep together the components because it has many advantages. The simplest example of adhesive assembly is a single lap joint. In the literature, the attention is focused on nominal adhesive assemblies, that do not represent the real products and that are tested to evaluate the product's strength. Therefore, the obtained mechanical performances are far from those connected with the real products. The present work takes into account the geometric deviations of a single lap joint, as the adherends' misalignment, due to the manufacturing process and used equipment on its strength. A numerical tool of the literature was modified to deal with adherends' misalignment to estimate both the tensile and the bending strength. The numerical results were validated through experimental tests. The developed numerical model shows a very low deviation from experimental results. The original contribution of this work is that the developed numerical model simulates the adhesive process of a real joint with adherends' misalignment and not of its nominal geometry; thus, providing a tool more useful in optics Industry 4.0 to represent a process closer to the real.
Keywords: Adhesive Joint; Adherends' Misalignment; Strength; Tensile Test; Bending Test